Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1001/archneur.55.10.1348
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Magnetic Resonance Imaging Findings in Spinocerebellar Ataxia 6

Abstract: The cerebellum and its afferent and efferent systems were affected in patients with SCA6. These results seem to distinguish the MRI findings of SCA6 from those of other forms of spinocerebellar ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 7 publications
5
37
1
1
Order By: Relevance
“…Mild pontine atrophy has been reported in a SCA6 patient with homozygocity [22]. Some authors pointed out mild pontine atrophy in heterozygote SCA6 patients [22, 23, 24]. This study clearly shows that heterozygote SCA6 can cause distinct pontine atrophy.…”
Section: Discussionsupporting
confidence: 64%
“…Mild pontine atrophy has been reported in a SCA6 patient with homozygocity [22]. Some authors pointed out mild pontine atrophy in heterozygote SCA6 patients [22, 23, 24]. This study clearly shows that heterozygote SCA6 can cause distinct pontine atrophy.…”
Section: Discussionsupporting
confidence: 64%
“…5,7,8 Although Murata et al 8 found a reduction of the anteroposterior diameter of the pons in patients with SCA6, results failed to show a correlation with CAG repeat length. The relationship between the volume changes and clinical dysfunction was not tested in this study.…”
Section: Discussionmentioning
confidence: 96%
“…8 On one hand, brain stem tissue loss was assessed by different techniques. In the present study, as well as in the study published by Schulz et al, 5 brain stem atrophy was quantified by using 3D MR imaging data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denier et al, 1999, Guida et al, 2001. Occasionally, at MRI, a size reduction of pons as well as of red nucleus and middle cerebellar peduncle has been reported (Murata et al, 1998;Arpa et al, 1999;Nakagawa et al, 1999). A widespread reduction of glucose metabolism at PET scan, with particularly low values in the brainstem and cerebellar hemispheres, was observed in a group of SCA6 patients as compared to normal controls (Soong et al, 2001b).…”
Section: Neuropathologymentioning
confidence: 97%